Prevalence of spin reporting bias in hip labrum reconstruction: a qualitative assessment of systematic reviews and meta-analyses - Gulbrandsen, Matthew T.; Cannon, Damien; M. Ong, Meng-Yung; Ruckle, David; Yalamanchili, Dheeraj; Essilfie, Anthony; Phipatanakul, Wesley; Liu, Joseph Nairne (International Journal of Research in Orthopaedics, 2024)
Hip labral reconstruction is an evolving technique to treat labral pathology. Spin is a recent concept that is defined as a reporting bias that misrepresents research. The purpose of this study is to identify the prevalence of spin in meta-analysis and systematic review abstracts regarding acetabular labral reconstruction. Electronic libraries were queried for meta-analyses and systematic reviews regarding hip labrum reconstruction. The nine most severe types of spin found in abstracts were used as an evaluation tool. Two reviewers each performed a blinded assessment of each article for spin. A third reviewer was used to address any discrepancies between the original reviewers. Other variables evaluated include number of citations, journal impact factor, reported conflicts of interest (COI), adherence to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, and methodologic quality according to a measurement tool to assess systematic reviews (AMSTAR-2). The electronic database search resulted in 1,148 articles, of which 10 met inclusion criteria. Of these 10 articles, 70% (7/10) were found to have at least one form of spin present, 20% (2/10) contained 3 different types of spin, 30% (3/10) contained 2 different types of spin, and 20% (2/10) contained 1 type of spin. The most common type of spin found was type 5, “conclusion claims the beneficial effect of the experimental treatment despite high risk of bias in the primary studies,” which was found in 60% (6/10) of the articles. When assessing AMSTAR-2 score, 90% (9/10) of the articles were found to be ‘low quality’ or ‘critically low quality.’ Spin was present in 70% of the abstracts of meta-analyses and systematic reviews pertaining to hip labrum reconstruction. Recognition of spin is crucial for orthopaedic surgeons. Improved guidelines should be considered to reduce the prevalence of spin in orthopaedic literature.